If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m/2+6=3
We move all terms to the left:
m/2+6-(3)=0
We add all the numbers together, and all the variables
m/2+3=0
We multiply all the terms by the denominator
m+3*2=0
We add all the numbers together, and all the variables
m+6=0
We move all terms containing m to the left, all other terms to the right
m=-6
| 29.8+y=20.25+14.8 | | x+.15x=89 | | 30m-12=10m+7 | | 2((n+0.6)+n)=2(n+0.1(2n)) | | 2(6x-1)+2(2+5=120 | | 37-7x=8(5-x) | | 10-8n=-94 | | 4r=45 | | 10=j/3+9 | | 80=1/6k+120 | | 3+y/4=-7/8 | | -82+g=16 | | 16x-5=14x1 | | 1/4(2-x)=12 | | X²-19x-90=0 | | X+3x=2650 | | 2(7)5x=26 | | 4(1+4x)=-19-7x | | -8a+10=25-4a) | | -2.5x-10=40 | | 6x+70+4x+140=x | | 7+3x=5x+1 | | 10x=5x-7 | | -10x+4=214 | | (y+3)/6=(y-2)/5 | | s-100=-2 | | 2x+5=x+14 | | -108n=-6n | | 20-c=12;8 | | 3+w/6=-4.68 | | 7b+4-2b=24 | | 5x-(-8x)+4x=-68 |